Design and rationale of the QUAZAR Lower-Risk MDS (AZA-MDS-003) trial: a randomized phase 3 study of CC-486 (oral azacitidine) plus best supportive care vs placebo plus best supportive care in patients with IPSS lower-risk myelodysplastic syndromes and poor prognosis due to red blood cell transfusion–dependent anemia and thrombocytopenia. Issue 1 (December 2016) - Garcia-Manero, Guillermo; Almeida, Antonio; Giagounidis, Aristoteles; Platzbecker, Uwe; Garcia, Regina; Voso, Maria; Larsen, Stephen; Valcarcel, David; Silverman, Lewis; Skikne, Barry; Santini, Valeria
Abstract Background CC-486 is an oral formulation of the epigenetic modifier azacitidine. In an expanded phase 1 trial, CC-486 demonstrated clinical and biological activity in patients with International Prognostic Scoring System (IPSS) lower-risk (low- and intermediate-1–risk) myelodysplastic syndromes (MDS) with poor prognostic features including anemia and/or thrombocytopenia who may have required red blood cell or platelet transfusions. The overall response rate was 40 %, including hematologic improvement in 28 % of patients and RBC transfusion independence sustained for 56 days in 47 % of patients with baseline transfusion dependence. Based on the results of this study, the randomized, placebo-controlled phase 3 QUAZAR Lower-Risk MDS trial (AZA-MDS-003) was initiated. The design and rationale for this trial comparing CC-486 with placebo for the treatment of patients with IPSS lower-risk MDS with poor prognostic features are described. Methods Patients must have IPSS lower-risk MDS with red blood cell (RBC) transfusion–dependent anemia and thrombocytopenia. Eligible patients are randomized 1:1 to receive 300 mg of CC-486 or placebo once daily for the first 21 days of 28-day treatment cycles. Disease status assessments occur at the end of cycle 6 and patients may continue to receive treatment unless there is evidence of progressive disease, lack of efficacy, or unacceptable toxicity. The primary endpoint is RBC transfusion independence for ≥ 84 days, assessed according to International Working Group 2006 criteria. Secondary endpoints include overall survival, hematologic response including platelet response and erythroid response, RBC transfusion independence for ≥ 56 days, duration of RBC transfusion independence, time to RBC transfusion independence, rate of acute myeloid leukemia (AML) progression, time to AML progression, clinically significant bleeding events, safety, health-related quality of life, and healthcare resource utilization. Conclusions This study will provide data on the efficacy and safety of CC-486 in the treatment of IPSS lower-risk MDS with poor prognosis due to the presence of both RBC transfusion–dependent anemia and thrombocytopenia. Positive results of the AZA-MDS-003 study may expand treatment options for patients with IPSS lower-risk MDS. Trial registration ClinicalTrials.govNCT01566695, registered March 27, 2012.